Řízení investičního projektu - Koukal, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Diplomová práce je zaměřena na hodnocení efektivnosti a proveditelnosti projektu. V teoretické části je popsána rozsáhlá problematika studie proveditelnosti. Dále se práce zabývá hodnocením efektivnosti projektu a jeho rizik. V praktické části je analyzován současný nevyhovující stav konkrétního stavebního objektu. Jsou navržena a zpracována dvě alternativní řešení projektu včetně jejich vyhodnocení. Tato řešení byla mezi sebou porovnána a předložena investorovi.

The diploma thesis is focused on evaluation of efficiency and feasibility of the project. In the theoretical part, there are described extensive issues of feasibility study. The thesis deals with evaluation of project effectiveness and its risks. The practical part analyzes the current unsatisfactory condition of a particular building. There are designed and processed two alternative solutions of the project including their evaluation. These solutions were compared with each other and presented to the investor.
Investment Project Management
Keywords: Investice; životní cyklus projektu; hodnocení efektivnosti; ukazatelé ekonomické efektivnosti; riziko; studie proveditelnosti; peněžní toky; financování.; Investment; project life cycle; evaluation of efficiency; indicators of economic efficiency; risk; feasibility study; cash flow; financing.